DOMESTIC MYOCARDIAL CYTOPROTECTOR EFFECTIVENESS AND ITS PHARMACODYNAMICS IN ACUTE MYOCARDIAL ISCHEMIA: CLINICAL RESULTS AND EXPERIMENTAL MODELS - V. P. Mikhin; M. V. Pokrovskyi; V. V. Gureev; O. A. Chernova; Yu. V. Alimenko; E. N. Bogoslovskaya (Российский кардиологический журнал)
Anti-ischemic effects of high-dose cardiac cytoprotector Mexicor (0,014 g/kg/d, 0,019 g/kg/d) were examined in rabbits with experimental myocardial infarction. In addition, anti-ischemic activity of Mexicor (0,4 g/d) was assessed in patients with acute coronary syndrome (ACS). It has been demonstrated that Mexicor reduced the size of infarction area and decreased the ratio “necrosis area / ischemia area”, compared to the control animals. In ACS patients, Mexicor facilitated faster recovery of left ventricular diastolic function, and also decreased blood levels of NT-proBNP.